A Biodiversity Hotspot Losing Its Biocultural Heritage: The Challenge to Biocultural Conservation of Brazilwood (Paubrasilia echinata) - Bastos, Juan Gomes; Kury, Lorelai; Hanazaki, Natalia; Capozzi, Rebeca; Fonseca-Kruel, Viviane Stern da (Frontiers in Forests and Global Change, 2022)
The biocultural heritage of a region is developed and adapted after centuries of interrelationship between humans and nature. The endangered brazilwood (Paubrasilia echinata (Lam.) E. Gagnon, H.C. Lima & G.P. Lewis) is a flagship species with cultural and economic importance, directly affected by the history of human occupation in Brazilian coast during and after the Portuguese colonization from the 16th century on. Besides its historical-cultural relevance, the lack of effective management and the anthropic pressure in coastal areas of the Brazilian Atlantic Forest (one of the terrestrial hotspots for biodiversity conservation) has led to the fragmentation of the landscape connectivity and to drastic degradation of the knowledge associated to the biodiversity, including brazilwood, also affecting the biocultural diversity of the region. In southeastern Brazil, in the region of Cabo Frio, state of Rio de Janeiro, there are fragments of forest remnants with genetically ancient populations of brazilwood (possibly from the colonization period). The recognition of this valuable natural and cultural heritage includes the establishment of protected areas in this region since 1986. Here we studied how the increasing of urbanization can affect the biocultural heritage of a flagship species even when close to Protected Areas. In nearby areas with populations of brazilwood, we interviewed residents from three communities: Peró and Jacaré (municipality of Cabo Frio), and José Gonçalves (municipality of Armação dos Búzios). We did semi-structured interviews and free lists, using visual stimuli to understand the current knowledge about this species. Thus, we verified a socio-ecological dissociation, both inside and outside the protected areas. This fact has brought the threat of losing the local knowledge network and the native populations of brazilwood in these areas, which consequently reveals the weaknesses of the current management models of the local protected areas. Despite this, we showed that the residents are interested in increasing local mobilization, awareness, environmental education, and reforestation actions aimed at the biocultural conservation of the species that gives the country its name, and of the Atlantic Forest biome.